Tirofiban for Branch Atheromatous Disease–Related Stroke - Yicong Wang; Xiaoling Liao; Shuo Feng; Yuesong Pan; Xuan Wang; Hui Qu; Yuetong Liu; Cong Gao; Xinru Liu; Qianqian Yang; Meiyang Zhang; Zhangxinyi Liu; et al. (JAMA Neurology, 2026)
Importance Patients with branch atheromatous disease (BAD)–related stroke are predisposed to early neurological deterioration (END) and disability. However, large-scale clinical trials focused on the prevention of the deterioration and recurrent stroke in this population are currently lacking. Objective To evaluate the efficacy and safety of intensive antiplatelet therapy combining the tirofiban with aspirin for patients with BAD-related stroke. Design, Setting, and Participants This randomized clinical trial was the multicenter, double-blind, randomized, placebo-controlled STRATEGY trial, conducted across 38 hospitals in China. Participants were patients with BAD-related acute ischemic stroke confirmed by magnetic resonance imaging within 48 hours of symptom onset were eligible for enrollment. Enrollment occurred from November 15, 2022, to November 19, 2024, with a 90-day follow-up period for all participants. Investigators, patients, and outcome assessors were blinded to treatment assignment. Interventions Eligible participants were randomized to receive either intravenous tirofiban or placebo (0.4 µg/kg/min for 30 minutes followed by 0.1 µg/kg/min for 24 hours). All patients received a 300-mg loading dose of aspirin on the day of randomization, followed by 100 mg daily until day 90. Main Outcomes and Measures The primary efficacy end point was END within 7 days or new stroke within 90 days. The primary safety end point was moderate or severe bleeding. Results Of 1378 patients with acute ischemic stroke screened for eligibility, 408 were excluded for ineligible imaging findings, other exclusion criteria, lack of consent, or additional reasons, leaving 970 participants who underwent randomization (486 assigned to tirofiban plus aspirin, 484 to placebo plus aspirin). The median (IQR) age was 63.0 (56.0-70.0) years; 607 patients (62.6%) were male and 363 (37.4%) female. The incidence of the primary efficacy end point was 79 patients (17.1%) in the tirofiban group and 89 (19.6%) in the placebo group (hazard ratio, 0.88; 95% CI, 0.65-1.19; P = .39). The incidence of the primary safety end point was 1 of 486 patients (0.2%) in the tirofiban group and 0 patients in the placebo group ( P > .99). Conclusions and Relevance This study found that in patients with BAD-related stroke, intravenous tirofiban combined with aspirin did not significantly reduce the risk of END or stroke compared with aspirin alone, nor was it associated with an increased risk of moderate or severe bleeding. Trial Registration ClinicalTrials.gov Identifier: NCT05310968